2019
DOI: 10.33594/000000007
|View full text |Cite
|
Sign up to set email alerts
|

Linoleic Acid Increases Prostaglandin E2 Release and Reduces Mitochondrial Respiration and Cell Viability in Human Trophoblast-Like Cells

Abstract: This article is licensed under the Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License (CC BY-NC-ND). Usage and distribution for commercial purposes as well as any distribution of modified material requires written permission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 67 publications
(86 reference statements)
1
8
0
Order By: Relevance
“…In an animal model of heart failure, LA has been shown to improve mitochondrial OXPHOS capacity in cultured rat cardiomyocytes ( Maekawa et al, 2019 ). Albeit being important for mitochondrial membrane integrity, high amounts of LA directly reduced the mitochondrial marker enzyme citrate synthase, as well as routine and maximal mitochondrial respiration in a concentration-dependent manner ( Shrestha et al, 2019 ). Furthermore, an excessive LA dietary intake leads to exacerbated arachidonic acid-derived lipid mediators, such as prostaglandin E 2 (PGE 2 ) and leukotriene B 4 (LTB 4 ) ( Shrestha et al, 2019 ).…”
Section: Changes In Plasma and Mitochondrial Membrane Lipid Composition In Patients With Cirrhosis—interplay Between Lipid Mediators And mentioning
confidence: 99%
See 1 more Smart Citation
“…In an animal model of heart failure, LA has been shown to improve mitochondrial OXPHOS capacity in cultured rat cardiomyocytes ( Maekawa et al, 2019 ). Albeit being important for mitochondrial membrane integrity, high amounts of LA directly reduced the mitochondrial marker enzyme citrate synthase, as well as routine and maximal mitochondrial respiration in a concentration-dependent manner ( Shrestha et al, 2019 ). Furthermore, an excessive LA dietary intake leads to exacerbated arachidonic acid-derived lipid mediators, such as prostaglandin E 2 (PGE 2 ) and leukotriene B 4 (LTB 4 ) ( Shrestha et al, 2019 ).…”
Section: Changes In Plasma and Mitochondrial Membrane Lipid Composition In Patients With Cirrhosis—interplay Between Lipid Mediators And mentioning
confidence: 99%
“…Albeit being important for mitochondrial membrane integrity, high amounts of LA directly reduced the mitochondrial marker enzyme citrate synthase, as well as routine and maximal mitochondrial respiration in a concentration-dependent manner ( Shrestha et al, 2019 ). Furthermore, an excessive LA dietary intake leads to exacerbated arachidonic acid-derived lipid mediators, such as prostaglandin E 2 (PGE 2 ) and leukotriene B 4 (LTB 4 ) ( Shrestha et al, 2019 ). In fact, this is clinically most relevant as patients with AD cirrhosis present with elevated levels of PGE 2 which suppresses macrophage pro-inflammatory cytokine secretion and bacterial killing, mediated via the prostanoid type E receptor-2 (EP2) ( O’Brien et al, 2014 ).…”
Section: Changes In Plasma and Mitochondrial Membrane Lipid Composition In Patients With Cirrhosis—interplay Between Lipid Mediators And mentioning
confidence: 99%
“…However, Draycott et al observed that fetal 13C-LA concentrations seem to be influenced by the total amount of FA in the maternal diet, more so than by the n-6 to n-3 ratio, concluding that a higher amount of total FA consumed would favor the placental transport of 13C-LA [114]. In addition, Shrestha et al [14] observed that the exposure to LA increased the expression of the transporters FATP1, FATP4, and FABP5 and decreased that of FABP3 in a culture of cytotrophoblasts, indicating that these proteins could regulate the transport of this PUFA. On the other hand, studies on the placental transport of 13C-LA are controversial, and it is still unclear whether maternal-fetal transfer is affected by obesity.…”
Section: Placental Fatty Acid Transportmentioning
confidence: 99%
“…Of these, n-3 and n-6 long chain PUFA (LCPUFA) are of particular interest because they are an integral part of cell membranes and participate in the synthesis of bioactive molecules that regulate multiple signaling pathways [13]. The supply of essential FA to the fetus will depend entirely on maternal consumption, placental transport and metabolism of FA [14]. Therefore, a balanced diet for pregnant and lactating women must in-clude an appropriate supply of FA.…”
Section: Introductionmentioning
confidence: 99%
“…Except for de novo synthesis and elongation of FA, the utilization of free FA is also a key step in lipid metabolism. FABP5 was found to be involved in the transport of large amounts of intracellular FAs into the nucleus to activate PPARG [28, 29]. Previous study indicated that upregulated FABP5 might contribute to excessive fat deposition in domestic ducks [30].…”
Section: Discussionmentioning
confidence: 99%